Hybrid Fringes. Discussing contemporary (r-)urban fractal territories: Techno-natural tactics for post-urban systems - Betta, Alessandro (Università degli studi di Trento, 2020)
Contemporary debate on the future of urban areas is open and far from finding a convergence point among disciplines. As environmental concerns rise globally and connections between urbanity and ecology are being developed, urban-rural fringes are still an overlooked territory. The thesis proposes a shift in the focus as traditional frameworks have proven to be inadequate to track land-use changes in these hybrid spaces. Starting from selected key concepts, a compelling narrative on hybrid urban-rural fringes is proposed. The thesis benefited from the work done within the Interreg Alpine Space project “Los_Dama!”. This allowed to bridge the gap between research and practice and to directly investigate local planning tools in their adoption process to understand the approach to urban-rural fringes and investigate the role of agriculture. The comparison of the tools and direct fieldwork with local stakeholders supported the understanding of barriers in the implementation of hybrid performative landscapes.